SAT0298 Patients' Perspective on the Reasons for Non-Treatment of Osteoporosis Among Postmenopausal Patients in France–An Observational Study. (9th June 2015) - Sadasivan, R.; Olsson, K.; Weaver, J.; Sen, S.; Modi, A.
Abstract : Background: Osteoporosis (OP) is a common chronic condition in postmenopausal women. Recent studies indicate that 10% 1 to 46% 2 of postmenopausal patients in France are not treated with prescription medications for OP, post diagnosis. Perceived barriers to receiving OP treatments need to be better understood to help reduce non-treatment rates. Objectives: To understand reasons for non-treatment from the perspective of post-menopausal OP patients in France. Methods: An online survey was conducted among postmenopausal patients in France who were newly diagnosed with OP (within the past 3-12 months) and who had not yet received prescription OP medication. The online survey was developed via a targeted literature review and pilot tested with patients prior to data collection.The survey was fielded from November 21 2014 to January 16, 2015. Descriptive analysis was conducted to understand patient characteristics and reasons for non-treatment. Results: 47 patients completed the patient survey (targeted sample size 100). Most patientswere aged 56-65 years (79%) and were retired (57%). The majority of patients (64%) were diagnosed via bone mineral density (BMD) scans. On average, patients had been untreated for 9.2 months (median: 10 months) post-diagnosis.From the patients' point of view, the primary reason for non-treatment was physician driven [physician decided not to prescribe (77%, n=36)], rather than patient driven [patient resisted the recommended prescription (23%, n=11)]. Patients reported that their physicians did not prescribe the medication for the following reasons: patient OP was not serious/borderline cases (56%), low calcium and/or vitamin D levels (19%), pre-existing gastrointestinal problems (19%). Among the few patients (n=11) who resisted the recommended medications, key reasons for resistance included: consideration of non-prescription options and behavioral modifications before prescription medications (64%) and concerns about medication side-effects (55%). Following the diagnosis of OP, the majority of patients (81%) were not directed to any additional source of information on OP management or treatment. However, if more information were provided by the physician, 49% of patients reported that they would be very likely to take the recommended OP medications. Conclusions: Based on the patient's perspective, the absence of treatment for OP wasmainly due to physician-driven factors. Clinical issues such as borderline cases (56%), low calcium and/or vitamin D levels (19%), pre-existing gastrointestinal problems (19%) were the major physician-led reasons for non-treatment. References: Cortet B. Use of strontium as a treatment method for osteoporosis. Curr Osteoporos Rep. 2011;9(1):25-30. Modi A, Fan T, Sajjan S, Rajagopalan S, Sen S. Characteristics and treatment initiation among women diagnosed with osteoporosis in France. Osteoporosis International. 2012;23:S194. Disclosure of Interest: R. Sadasivan Employee of: Evidera, K. Olsson Employee of: Evidera, J. Weaver Employee of: Merck & Co Inc, S. Sen Employee of: Merck & Co Inc, A. Modi Employee of: Merck & Co Inc